Students Perception towards Movie to Enhance Speaking Skills Ability in British Accents - Kusuma, Arzeviningsih Indrasdi; Rokhayati, Titi; Johan, Andrian Nuriza (Universitas Nurul Jadid, 2025)
This research aims to find out students’ perceptions of movie towards speaking skills ability in British accents at SMA N 6 Purworejo. This research used descriptive qualitative design. The subject in this research was class X-4 students of SMA N 6 Purworejo with a total number of 34 students. An interview required to collect data from the participants, it is used to get information from students. The questions of interviews of this research consisted of 10 questions. The results showed that students prefer learning English with movie and this 1917 movie can made students understand British accents but cannot enhance their speaking skill ability. The data proved that the students’ perception towards movie had positive reaction and all statements from students can be used as evidence. The researchers suggested that students should often use learning media to enhance their speaking skills ability, especially movies, they are easy and practical because it can help students when practicing speaking.